Potential Role of Carvedilol in the Cardiac Immune Response Induced by Experimental Infection with Trypanosoma cruzi. (9th March 2017) - Horta, Aline Luciano; Leite, Ana Luisa Junqueira; Paula Costa, G.; Figueiredo, Vivian Paulino; Talvani, André
Abstract : Trypanosoma cruzi causes a cardiac infection characterized by an inflammatory imbalance that could become the inciting factor of the illness. To this end, we evaluated the role of carvedilol, a beta-blocker with potential immunomodulatory properties, on the immune response in C57BL/6 mice infected with VL-10 strain of T. cruzi in the acute phase. Animals (n = 40 ) were grouped: (i) not infected, (ii) infected, (iii) infected + carvedilol, and (iv) not infected + carvedilol. We analyzed parameters related to parasitemia, plasma levels of TNF, IL-10, and CCL2, and cardiac histopathology after the administration of carvedilol for 30 days. We did not observe differences in the maximum peaks of parasitemia in the day of their detection among the groups. The plasma TNF was elevated at 60 days of infection in mice treated or not with carvedilol. However, we observed a decreased CCL2 level and increased IL-10 levels in those infected animals treated with carvedilol, which impacted the reduction of the inflammatory infiltration in cardiac tissue. For this experimental model, carvedilol therapy was not able to alter the levels of circulating parasites but modulates the pattern of CCL2 and IL-10 mediators when the VL10 strain of T. cruzi was used in C57BL6 mice.